Tính:
1\(\frac{5}{8}\):13=.................................................
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1/13. 8/13 - 14/13 + 5/13 .1/13
= 1/13. ( 8/13+5/13) -14/13
= 1/13. 13/13-14/13
= 1/13 . 1 - 14/13
= 1/13-14/13
= -13/13
= -1
k cho mik nhoa
1/13. 8/13 - 14/13 + 5/13 .1/13
= 1/13. ( 8/13+5/13) -14/13
= 1/13. 13/13-14/13
= 1/13 . 1 - 14/13
= 1/13-14/13
= -13/13
= -1
\(\frac{\frac{3}{7}-\frac{3}{11}+\frac{3}{13}}{\frac{5}{7}-\frac{5}{11}+\frac{5}{13}}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}}{\frac{5}{4}-\frac{5}{6}+\frac{5}{8}}\)
\(=\frac{3\left(\frac{1}{7}-\frac{1}{11}+\frac{1}{13}\right)}{5\left(\frac{1}{7}-\frac{1}{11}+\frac{1}{13}\right)}+\frac{4\left(\frac{1}{4}-\frac{1}{6}+\frac{1}{8}\right)}{5\left(\frac{1}{4}-\frac{1}{6}+\frac{1}{8}\right)}\)
\(=\frac{3}{5}+\frac{4}{5}=\frac{7}{5}\)
Ta có: \(\frac{\frac{3}{7}-\frac{3}{11}+\frac{3}{13}}{\frac{5}{7}-\frac{5}{11}+\frac{5}{13}}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}}{\frac{5}{4}-\frac{5}{6}+\frac{5}{8}}\)
\(=\frac{3\left(\frac{1}{7}-\frac{1}{11}+\frac{1}{13}\right)}{5\left(\frac{1}{7}-\frac{1}{11}+\frac{1}{13}\right)}+\frac{4\left(\frac{1}{4}-\frac{1}{6}+\frac{1}{8}\right)}{5\left(\frac{1}{4}-\frac{1}{6}+\frac{1}{8}\right)}\)
\(=\frac{3}{5}+\frac{4}{5}\)
\(=\frac{7}{5}\)
ta có \(\frac{\frac{3}{7}-\frac{3}{11}+\frac{3}{13}}{\frac{5}{7}-\frac{5}{11}+\frac{5}{13}}=\frac{3\left(\frac{1}{7}-\frac{1}{11}+\frac{1}{13}\right)}{5\left(\frac{1}{7}-\frac{1}{11}+\frac{1}{13}\right)}=\frac{3}{5}\)
và \(\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}}{\frac{5}{4}+\frac{5}{8}-\frac{5}{6}}=\frac{2\left(\frac{1}{2.2}-\frac{1}{3.2}+\frac{1}{4.2}\right)}{5\left(\frac{1}{4}+\frac{1}{8}-\frac{1}{6}\right)}=\frac{2\left(\frac{1}{4}+\frac{1}{8}-\frac{1}{6}\right)}{5\left(\frac{1}{4}+\frac{1}{8}-\frac{1}{6}\right)}=\frac{2}{5}\)
Vậy \(\frac{\frac{3}{7}-\frac{3}{11}+\frac{3}{13}}{\frac{5}{7}-\frac{5}{11}+\frac{5}{13}}+\frac{\frac{1}{2}-\frac{1}{3}+\frac{1}{4}}{\frac{5}{4}+\frac{5}{8}-\frac{5}{6}}=\frac{3}{5}+\frac{2}{5}=\frac{5}{5}=1\)
ĐS: 1
\(A=\frac{7\times9+14\times27+21\times36}{21\times27+42\times81+63\times108}=\frac{7\times9+7\times2\times9\times3+7\times3\times9\times4}{21\times27+21\times2\times27\times3+21\times3\times27\times4}=\frac{7\times9\times\left(1+2\times3+3\times4\right)}{21\times27\times\left(1+2\times3\times3\times4\right)}=\frac{7\times3\times3}{7\times3\times3\times9}=\frac{1}{9}\)
\(\frac{5}{13}+-\frac{5}{17}+-\frac{20}{41}+\frac{8}{13}+-\frac{21}{41}\)
\(=\left(\frac{5}{13}+\frac{8}{13}\right)+\left(-\frac{20}{41}+-\frac{21}{41}\right)+-\frac{5}{17}\)
\(=1+\left(-1\right)+-\frac{5}{17}\)
\(=0+-\frac{5}{17}\)\(=-\frac{5}{17}\)
Ủng hộ tk Đúng nhé mọi người !!! ^^
Trả lời:
1 5/8 : 13 = 13/8 : 13 = 1/8
HT~
\(1\frac{5}{8}:13\)
\(=\frac{13}{8}:13\)
\(=\frac{1}{8}\)